Employing metrics of effectiveness in the capital structure management of an enterprise - Joanna Wieprow (Economic and Environmental Studies (E&ES), 2017)
Effectiveness metrics can be employed in the management of capital structure in an enterprise understood as a relationship between equity and liabilities on which interest is paid. In using the measures, it is possible to analyze and evaluate capital structure, and also to strive for its optimization. An optimal capital structure reduces the weighted average cost of capital, thus affecting the increase in the enterprise value. Determining capital structure is one of the elements involved in the finance strategy employed in an enterprise. The measures relating to capital structure that are most frequently applied include: measures based on the criterion of the value of equity, capital structure indicator, degree of financial leverage, return on equity and weighted average cost of capital. The paper's objective is to determine the relevance of effectiveness measures in the capital structure-shaping process. It is written drawing on specialist literature covering the topics discussed. Moreover, an analysis, in the form of a case study, is conducted with regard to selected enterprise effectiveness measures relating to determining capital structure. The said analysis is conducted based on the consolidated financial statement of Ursus S.A., a joint stock company, over the period of 2014- 2016.
Keywords: G31; G32; 330; capital structure; enterprise effectiveness; effectiveness metrics; finance strategy